Seriam os epibiontes uma representação do status de saúde das tartarugas-verdes (Chelonia mydas)? - Silva, Fernanda Felisbino Ferreira da (2021)
Orientador: Prof. Dr. Gustavo Fernandes Camargo Fonseca